DataNet: linking multi-faceted building energy datasets for effective performance analysis at scale - Hye-Gi Kim; Hyery Shin; Han-Gyeong Chu; Dong Hyuk Yi; Sang-Lin Park; Doosung Kim; Hyunwoo Lim; Sungmin Yoon; Eui-Jong Kim; Jaewan Joe; Sunsook Kim; Hyeunguk Ahn; et al. (Energy and Buildings, 2026)

Strong vorticity beneath the gas-liquid contact area accelerates carbon dioxide absorption - Wonyoung Choi; Ilyoup Sohn; Jong-In Han (Journal of Environmental Chemical Engineering, 2026)

Comparative responses of fruit quality attributes, mineral nutrients, and targeted metabolites in fruit of early- to mid-season apple cultivars at harvest - Jinhee Lee; Hnin Phyu Lwin; Seung Yeon Han; Si-Eun Byeon; Hyowon Park; Theint Thandar Latt; Jiwon Park; Sooyeon Lim; Jong Taek Park; Ha-il Jung; Dagyeong Kwon; Jeong Hee Kim; et al. (Horticulture, Environment, and Biotechnology, 2026)

Preliminary Study on Broodstock Management, Inducing Natural Spawning and Larval Rearing of Silver Pomfret, Pampus argenteus - In Joon Hwang; Jong Cheol Han (Fishes, 2026)
Silver pomfret (Pampus argenteus, family Stromateidae) is a highly valuable marine fish species with significant commercial demand; however, its aquaculture remains undeveloped due to limited knowledge of captive breeding and seed production. To our knowledge, this is the first successful report on the induction of maturation, natural spawning, and larval rearing of silver pomfret under captive conditions in Korea. Wild broodstock (33 individuals in 2020; 250 individuals in 2021) were collected from the southern coastal waters of Korea using set nets. In the first year, water temperature management alone successfully induced gonadal maturation, as evidenced by a significant increase in the gonadosomatic index (GSI) and the presence of vitellogenic oocytes (400–500 μm) in April. In the second year, natural spawning was observed on fifteen occasions from May to September 2022, yielding a total number of 157,050 eggs. Fertilized eggs were spherical, transparent, and pelagic, with diameters ranging from 1.29 to 1.37 mm. Hatched larvae (total length: 4.85 ± 0.22 mm) exhibited poor feeding responses to rotifers and high early mortality within two weeks post-hatching, with the maximum rearing period reaching 24 days post-hatching. These findings demonstrate that water temperature management alone is sufficient to induce maturation and natural spawning of silver pomfret, and highlight the critical need for optimizing larval feeds, improving broodstock nutritional management, and conducting endocrine profiling during reproduction to establish a complete aquaculture protocol for this species.

A 13-week repeated oral toxicity study of Mycoleptodonoides aitchisonii (Agaricomycetes) in Sprague–Dawley rats - In-Hyeon Kim; Sung-Hwan Kim; Joung-Wook Seo; Young-Ju Lee; Han Na Suh; Jong-Choon Kim (Toxicological Research, 2026)

Facile eco-friendly sol-gel synthesis of highly monodispersed Zn@silica nanospheres with dual antibacterial mechanism against multidrug-resistant bacteria - Yesul Jeong; Hyeran Kim; Soon Chang Lee; Ha-Rim An; Jong-Seong Bae; Yunju Choi; Byoungchul Son; Ji-In Park; Da-Hye Kim; Jiwon Seo; Eui-Jeong Han; Ji-Hyun Lee; et al. (Chemical Engineering Journal, 2026)

Regeneration of Fe(II) EDTA by S(IV) oxyanions and electrochemical reduction: Lowering Fe(II)EDTA-NO/Fe(II) EDTA ratio to maximize DeNOX performance - Beomseo Kim; DongYeon Kim; Jong-In Han (Chemical Engineering Journal, 2026)

Energy-efficient direct air capture combining an impeller-based scrubber and anion exchange membrane electrolysis - Sunghyeon Han; Jongmin Jin; Hui Song; Jong-In Han (Chemical Engineering Journal, 2025)

Impeller-driven scrubber system for enhanced nitric oxide capture using Fe(II)EDTA - Shin Han; Hyun-Woo Kim; Gwangtaek Lee; Sunghyeon Han; Jong-In Han (Journal of Environmental Chemical Engineering, 2025)

Improving acid-free and selective leaching of lithium from end-of-life LiFePO4 batteries using sodium persulfate: Impact of removing organic matter by thermal treatment in an inert atmosphere - Jong-Won Choi; Mooki Bae; Hyunju Lee; Hong-In Kim; Hyun-Woo Shim; Jinyoung Je; Gigap Han; Junhyun Choi; Hyunjoon Lee; Sookyung Kim (Hydrometallurgy, 2025)

Spatiotemporally adjustable hybrid hydrogels interconnected by 2D MXene for combinatorial therapy of infected diabetic wounds - Mrinmoy Karmakar; Sungyun Kim; Han-Jun Kim; Ji Won Huh; Da In Jeong; Eunseo Park; Seongeun Kim; Eun-Hye Hong; Jin Hyeong; Dae-Joon Kim; Hye Kyu Choi; Junmin Lee; et al. (Chemical Engineering Journal, 2025)

Systemic toxicity and toxicokinetics study of self-assembled-micelle inhibitory RNA-targeting amphiregulin in cynomolgus monkeys following intravenous injection - Hyeon-Young Kim; Tae-Rim Kim; Sung-Hwan Kim; In-Hyeon Kim; Woong-Il Kim; Jun-Hong Park; Youngho Ko; Sungil Yun; Han-Oh Park; Jong-Choon Kim (Toxicological Research, 2025)

Coupling nitric oxide capture with ammonia production using Fe(II)(DMPS)2 in the impeller-based wet nitric oxide absorption process - Hyun-Woo Kim; Kwiyong Kim; Ilgyu Lee; Gwangtaek Lee; Seonjeong Cheon; Jong-In Han (Chemical Engineering Journal, 2025)

Transcriptome-Based Prediction of the Toxicity of the Marine Biotoxin Okadaic Acid in Human Vascular Endothelial Cells - Jong Hee Kim; Jeong-In Park; Yewon Kim; Mira Park; Jang Kyun Kim; Young-Seok Han; Youn-Jung Kim (Ocean Science Journal, 2025)

Investigating uncertainties in air quality models used in GMAP/SIJAQ 2021 field campaign: General performance of different models and ensemble results - Yesol Cha; Jong-Jae Lee; Chul Han Song; Soontae Kim; Rokjin J. Park; Myong-In Lee; Jung-Hun Woo; Jae-Ho Choi; Kangho Bae; Jinhyeok Yu; Eunhye Kim; Hyeonmin Kim; et al. (Atmospheric Environment, 2025)

Effects of the physical structure and surface charge of activated carbon on the reduction of biogenic amines in anchovy fish sauce - Kil Bo Shim; Jung-Jin In; Jong Bong Lee; Hyeong Gu Han; Seong Ah Son; Woo Jin Lee; Yeon Joo Bae; Ga Yeon Kwon; Byoung Kyu An (Food Chemistry, 2024)

Unique photothermal material: Copper phosphate (Cu3P2O8) with broadband visible-to-near-infrared absorption properties for efficient solar steam generation - Tatachari Santhanagopalan Shridharan; Jong Ho Lee; Runfa Tan; Arumugam Sivanantham; Hyun Soo Han; Hyun Suk Jung; In Sun Cho (Desalination, 2024)

Two-in-one strategy: Discretely functionalized electrolyte additive for stable lithium metal batteries coupled with Ni-rich cathode - Yong Min Kim; Jeong In Choi; Bo Keun Park; Ji Woo Han; Jong-Won Lee; Hyun-seung Kim; Ki Jae Kim (Chemical Engineering Journal, 2024)

Direct recovery of electro-synthesized ammonia from low-concentration nitric oxide using pulse electrodeposited Cu/C catalyst in a catholyte-free system - Hyun-Woo Kim; Jongmin Jin; Marieandre Kim; Kwiyong Kim; Jong-In Han (Chemical Engineering Journal, 2024)

Optimizing electroactive membrane performance for microalgae harvesting: A response surface methodology study of membrane formulation and operating parameters for electro filtration - Azeem Mushtaq; Hoon Cho; Asma Batool; Muhammad Tahir Fazal; Muhammad Aslam; Muhammad Saif UR. Rehman; Jason Chun-Ho Lam; Jong-In Han (Chemosphere, 2024)

Electrochemically-mediated reactive separation of nitric oxide into nitrate using iron chelate - SeokHwan Jeon; Mintaek Im; Kwiyong Kim; DongYeon Kim; Jong-In Han (Chemosphere, 2023)

Design strategy of cathodic electrocatalysts to effectively suppress inorganic fouling for long-term stability of reverse electrodialysis - Eunjin Jwa; Hanki Kim; Joo-Youn Nam; Jong-In Han; Namjo Jeong (Chemical Engineering Journal, 2023)

Energy-efficient electrochemical recovery of gold enabled by a thiourea-based electrolyte system - Jieun Son; Jong-In Han; Yeongran Hong; Cafer T. Yavuz (Journal of Environmental Chemical Engineering, 2023)

Effects of Immunostimulants, Prebiotics, Probiotics, Synbiotics, and Potentially Immunoreactive Feed Additives on Olive Flounder ( Paralichthys olivaceus ): A Review - Md Tawheed Hasan; Won Je Jang; Jong Min Lee; Bong-Joo Lee; Sang Woo Hur; Sang Gu Lim; Kang Woong Kim; Hyon-Sob Han; In-Soo Kong (Reviews in Fisheries Science & Aquaculture, 2019)

Allelic variation in Brassica oleracea CIRCADIAN CLOCK ASSOCIATED 1 (BoCCA1) is associated with freezing tolerance - Hayoung Song; Hankuil Yi; Ching-Tack Han; Jong-In Park; Yoonkang Hur (Horticulture, Environment, and Biotechnology, 2018)

Development of an Observation Processing Package for Data Assimilation in KIAPS - Jeon-Ho Kang; Hyoung-Wook Chun; Sihye Lee; Ji-Hyun Ha; Hyo-Jong Song; In-Hyuk Kwon; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Tae-Hun Kim (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Development of an Operational Hybrid Data Assimilation System at KIAPS - In-Hyuk Kwon; Hyo-Jong Song; Ji-Hyun Ha; Hyoung-Wook Chun; Jeon-Ho Kang; Sihye Lee; Sujeong Lim; Youngsoon Jo; Hyun-Jun Han; Hanbyeol Jeong; Hui-Nae Kwon; Seoleun Shin; et al. (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Resistance exercise improves cardiac function and mitochondrial efficiency in diabetic rat hearts - Tae Hee Ko; Jubert C. Marquez; Hyoung Kyu Kim; Seung Hun Jeong; SungRyul Lee; Jae Boum Youm; In Sung Song; Dae Yun Seo; Hye Jin Kim; Du Nam Won; Kyoung Im Cho; Mun Gi Choi; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Lipid induction of Chlamydomonas reinhardtii CC-124 using bicarbonate ion - Kibok Nam; Ara Jo; Yong Keun Chang; Jong-In Han (Journal of Applied Phycology, 2018)

Cultivation of Chlorella vulgaris with swine wastewater and potential for algal biodiesel production - Kibok Nam; Hansol Lee; Sung-Woon Heo; Yong Keun Chang; Jong-In Han (Journal of Applied Phycology, 2017)

Inhibitory effect of snake venom toxin on NF-κB activity prevents human cervical cancer cell growth via increase of death receptor 3 and 5 expression - Hye Lim Lee; Mi Hee Park; Ji Eun Hong; Dae Hwan Kim; Ji Young Kim; Hyen Ok Seo; Sang-Bae Han; Joo Hee Yoon; Won Hyoung Lee; Ho Sueb Song; Ji In Lee; Ung Soo Lee; et al. (Archives of Toxicology, 2016)

OsREL2, a rice TOPLESS homolog functions in axillary meristem development in rice inflorescence - Yerim Kwon; Si-in Yu; Joo-hyuk Park; Ying Li; Jin-Hee Han; Hemasundar Alavilli; Jung-Il Cho; Tae-Houn Kim; Jong-Seong Jeon; Byeong-ha Lee (Plant Biotechnology Reports, 2012)

5-Phenylselenyl- and 5-methylselenyl-methyl-2′-deoxyuridine induce oxidative stress, DNA damage, and caspase-2-dependent apoptosis in cancer cells - Byeong Mo Kim; Ambadas B. Rode; Eun Jong Han; In Seok Hong; Sung Hee Hong (Apoptosis, 2012)

A genome-wide association analysis reveals 1p31 and 2p13.3 as susceptibility loci for Kawasaki disease - Jae-Jung Kim; Young Mi Hong; Saejung Sohn; Gi Young Jang; Kee-Soo Ha; Sin Weon Yun; Myung Ki Han; Kyung-Yil Lee; Min Seob Song; Hyoung Doo Lee; Dong Soo Kim; Jong-Eun Lee; et al. (Human Genetics, 2011)

Extract of Poncirus trifoliata fruit reduces elevated serum IgE concentrations in chemically induced allergic model mice - Hyun Jung Park; Jong Bo Kim; In Song Han; Jin Hoi Kim; Bokyung Kim; Sung-Ho Kang; Ho-Sung Jung; Sang Ho Moon; Si Heung Sung; Hyuk Song (Horticulture, Environment, and Biotechnology, 2011)

Performance of microbial fuel cell with volatile fatty acids from food wastes - Jin-dal-rae Choi; Ho Nam Chang; Jong-In Han (Biotechnology Letters, 2011)

Seasonal volume transport variation in the Tsushima Warm Current through the Tsushima Straits from 10 years of ADCP observations - Ken-Ichi Fukudome; Jong-Hwan Yoon; Alexander Ostrovskii; Tetsutaro Takikawa; In-Seong Han (Journal of Oceanography, 2010)

Experience-Dependent Plasticity of Cerebellar Vermis in Basketball Players - In Sung Park; Kea Joo Lee; Jong Woo Han; Nam Joon Lee; Won Teak Lee; Kyung Ah Park; Im Joo Rhyu (The Cerebellum, 2009)

A single chamber stackable microbial fuel cell with air cathode - Bin Wang; Jong-In Han (Biotechnology Letters, 2009)

15-Deoxy-Δ12,14-prostaglandin J2 (15d-PGJ2) sensitizes human leukemic HL-60 cells to tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis through Akt downregulation - Hoon Han; Sung-Won Shin; Chi-Yeon Seo; Hyuk-Chan Kwon; Jin-Yeong Han; In-Hoo Kim; Jong-Young Kwak; Joo-In Park (Apoptosis, 2007)

Utilization of homoserine lactone as a sole source of carbon and energy by soil Arthrobacter and Burkholderia species - Wan-Wan Yang; Jong-In Han; Jared Renton Leadbetter (Archives of Microbiology, 2006)

Quantification of gene expression in methanotrophs by competitive reverse transcription‐polymerase chain reaction - Jong‐In Han; Jeremy D. Semrau (Environmental Microbiology, 2004)
Summary To improve the monitoring of methanotrophic activity, a competitive reverse transcription‐polymerase chain reaction (RT‐PCR) methodology was developed. Homologous internal RNA standards were created for mmoX and pmoA , genes encoding polypeptides of sMMO and pMMO, respectively. Using specific primer sets, expression of sMMO and pMMO could be quantified by means of competitive RT‐PCR and capillary electrophoresis with uncoated bare‐fused silica columns and UV detection. Using this technique, it was discovered that the amount of mRNA transcript for both mmoX and pmoA correlated well with whole‐cell sMMO and pMMO activity respectively. A method for soil RNA extraction was also developed to utilize this RNA quantification technique for the monitoring of methanotrophic activity in situ . In a model soil slurry system with a background concentration of 2.9 µM copper, it was found that only pmoA was transcribed by cells capable of expressing both forms of MMO. As pMMO and sMMO have very different substrate ranges and kinetics, this methodology may prove useful for optimizing in situ bioremediation by methanotrophs. Provided sufficient sequence information is available to create specific primer sets, these techniques can be applied for monitoring and measuring the activity of other microbial communities in situ .

Embryo lethality and teratogenicity of a new fluoroquinolone antibacterial DW-116 in rats - Jong-Choon Kim; Hyo-In Yun; Ho-Chul Shin; Sang-Seop Han; Moon-Koo Chung (Archives of Toxicology, 2000)